GAMBARAN TINGKAT KEPUASAN PASIEN TERHADAP KUALITAS PELAYANAN KESEHATAN DI POLIKLINIK GIGI DAN MULUT RUMAH SAKIT UMUM PURI RAHARJA - Yogi Darma Raharja; Sari Kusumadewi; Dewi Puri Astiti (Odonto : Dental Journal, 2018)
Background: Patient satisfaction on health service quality are comparisonbetween patient perception before receiving service and after service received. High patient satisfaction will be achieved if the patient’s expectation before receiving the service is fulflled. Patient’s expectations will be fulflled if the services provided exceed quality, therefore, patient satisfaction is key marker of the quality health service. This aims of this study was to determine the description level of patient satisfaction to health services quality on Dental Polyclinic at Puri Raharja General Hospital.Method: This study was a quantitative descriptive study with cross-sectional research design. The sampling method used was consecutive sampling with total sample 66 respondents. The datas were collected using questionnaires that had been tested for validity and reliability to determine patient satisfaction level to health service quality in fve SERVQUAL dimension: tangibles, reliability, responsiveness, assurance and empathy.Result: The results showed 57 respondent (86,4%) satisfed with the quality of health services provided. In each dimension, the majority of respondents were satisfed except in the tangibles dimension.Conclusion: Majority of patients who visited Dental Polyclinic at Puri Raharja General Hospital satisfed with the service given, except in the tangibles dimension, where 48,5% patient were unsatisfed